Asuhan keperawatan diare pada anak dengan pemberian terapi madu - Novindri Ryalita; Linawati Novikasari; Aryanti Wardiyah (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Diarrhea is a common health problem among children and can lead to dehydration and even death if not managed properly. In addition to medical treatment, natural therapies such as honey administration have the potential to accelerate recovery. Honey is known to have antimicrobial properties and can help restore fluid and electrolyte balance. Purpose: to describe nursing care for children with diarrhea who were given honey as a complementary therapy as part of independent nursing interventions. Method: This research uses a case study approach with a sample of two pediatric patients experiencing diarrhea. Data collection was conducted through interviews, observation, and documentation review. The nursing care process included assessment, nursing diagnosis, planning, implementation, and evaluation, with a focus on the administration of honey over a period of three days, given three times a day in the morning, afternoon, and evening at a dose of 2.5 ml each time. Result: After three days of honey administration, both patients showed improvement in the severity of diarrhea. Initially, both were categorized as having severe diarrhea. Following the intervention, their condition improved to mild diarrhea. The frequency of bowel movements decreased from 7 and 6 times (pre-test) to 2 and 3 times (post-test), and stool consistency changed from watery to solid. Conclusion: Honey therapy has been proven to help accelerate the healing process in children with diarrhea. This intervention can serve as a safe and easily applied alternative for independent nursing care